(untitled) (Journal of Human Sciences, 2021)
This study aimed to identify the degree to which faculty members at the brack college of education possess educational competencies from their point of view based on the following variables : academic degree, years of experience and academic qualification. The study sample consisted of (31) faculty members. The study tool is a questionnaire that consisted of (27) varied adequacies. The results showed that the faculty members’ possession of educational competencies came to a high degree with a percentage of (83.35), and the results showed that there were no statistically significant differences according to the variables of academic degree, years of experience and academic qualification. The study was concluded with some recommendations and suggestions.